A circle touches two sides of a triangle and two of its medians. Prove that the triangle is isosceles.


This problem came from the Mathematical Digest issue 62 (Jan 1986) which in turn cited a Russian mag called KVANT (meaning "Quantum").

  • 16
    $\begingroup$ Assume it's not true. Then you wouldn't ask the question. A contradiction. Therefore it's true. QED. :) $\endgroup$
    – SteveV
    Commented Mar 13, 2021 at 1:02

3 Answers 3


As the triangles ADC and BEC have the same incircle and their areas are equal (half that of ABC), so are their perimeters
or, subtracting from both sides CD+CE+DA+EB
This means that D and E lie on the same pair of hyperbolas with foci A and B. Since they also have the same distance to the base AB (half that of C) the triangle must be isosceles by symmetry.

  • 2
    $\begingroup$ It took me a moment to see why they have the same distance to the base, but that should have been obvious. This is a really clever proof. $\endgroup$ Commented Mar 13, 2021 at 8:38
  • 1
    $\begingroup$ @JaapScherphuis It's short ;-) I've added a half sentence explaining (if you can call it that) the distance to the base. $\endgroup$
    – loopy walt
    Commented Mar 13, 2021 at 9:50
  • $\begingroup$ That is clever. I don't think I've ever seen anyone use a hyperbola locus in a proof like this! $\endgroup$
    – Dr Xorile
    Commented Mar 13, 2021 at 17:34
  • $\begingroup$ Elegant, indeed. $\endgroup$ Commented Mar 16, 2021 at 6:16

Alternative Proof

By Pitot Theorem we have $|CE|+|MD| = |CD|+|ME|$ and since the centroid divides each median in the ratio 2:1, this means that $$\frac{1}{2}|AC| + \frac{1}{3}|AD| = \frac{1}{2}|BC|+\frac{1}{3}|BE|$$ Now let $|AB| = c, |BC| = a, |CA|=b, |AD|=m_a, |BE|=m_b$.
Then Apollonius' Theorem tells us that $$m_a = \sqrt{\frac{2b^2+2c^2-a^2}{4}}\,\,\,\,,\,\,\,\,m_b = \sqrt{\frac{2a^2+2c^2-b^2}{4}}$$ Substituting this in above and multiplying across by $6$ yields $$ 3a + \sqrt{2b^2+2c^2-a^2} = 3b + \sqrt{2a^2+2c^2-b^2}$$ $$\Rightarrow 3(a-b) + \sqrt{2b^2+2c^2-a^2} = \sqrt{2a^2+2c^2-b^2}$$ $$\Rightarrow 9(a-b)^2 + 6(a-b)\sqrt{2b^2+2c^2-a^2} + 2b^2+2c^2-a^2 = 2a^2+2c^2-b^2$$ $$\Rightarrow (a-b)\left(9(a-b) + 6\sqrt{2b^2+2c^2-a^2} - 3(a+b)\right) = 0$$ which means either $a=b$ or $\sqrt{2b^2+2c^2-a^2} = 2b-a$.
If it is the latter then $$2b^2+2c^2-a^2 = 4b^2-4ab+a^2 $$ $$\Rightarrow c^2 = b^2-2ab+a^2 = (b-a)^2$$ $$\Rightarrow c = \pm(b-a) $$ which only happens for a degenerate triangle (does not satisfy the triangle inequality).
Hence $a=b$


@loopwalt and @hexomino both gave excellent answers. I wanted to share the answer from the Mathematical Digest, because it's also elegant in its own way:

It starts the same way as @hexomino's proof (I didn't know it was called Pitot's Theorem!):

Since $CEMD$ circumscribes a circle, $CE+MD = CD + ME$ (Pitot's Theorem, but fun to prove). So (as in hexomino's proof):
$$\frac{1}{2}AC+\frac{1}{3}AD = \frac{1}{2}BC+\frac{1}{3}BE \tag1$$
Next, note that $\triangle ADC$ and $\triangle BEC$ have the same area ($\frac{1}{2}\triangle ABC$) and share a common incircle. This means that their perimeters are equal (another fun to prove and left as an exercise!). So $AD+\frac{1}{2}BC+AC = BE+\frac{1}{2}AC+BC$, which gives:
$$\frac{1}{2}AC+AD = \frac{1}{2}BC+BE \tag2$$
Now, $3\times(1)-(2)$ gives $AC=BC$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.